Efficacy of Mahapancha Gavya (MPG) in controlling damping-off in tomato caused by Pythium aphanidermatum - Kumar, Rakesh; Hooda, Indra; Karwasra, SS (Bangladesh Journal of Agricultural Research, 2010)
Maha Pancha Gavya (MPG), a concoction made from five cow products was tested for its toxicity against Pythium aphanidermatum (Edson) Fitz. and its antagonists at 5, 10, 25, and 50% concentration in in vitro to find out if it can be used in integration for the control of damping-off in tomato in nursery beds. MPG was very effective inihibiting the growth of P. aphanidermatum. At the highest concentration, the growth of the pathogen was negligible. Isolates of Trichoderma viride, T harzianum, and T. virens were also sensitive to MPG at all the concentrations. Their radial growth decreased, but it was fluffy in nature and sporulated profusely. MPG was not toxic against two bacterial antagonists i.e., Bacillus subtilis and Pseudomonas fluorescens. Soil application of 10% MPG to nursery beds improved seedling stand and gave upto 48.27% tlisease control, which was more than that given by individual antagonists. However, MPG improved disease control efficacy of all the antagonists when it was used in combination with them. Integrated treatment with MPG and B. subtilis gave maximum disease control (65.33%). MPG enhanced seedling growth and it was more in combination with T. viride and B. subtilis. MPG in integration with neem cake and neem leaf extract gave complete control of damping-off and maxium increase in height of the tomato seedlings. Keywords: Maha Panch Gavya (MPG); Trichoderma; Pythium aphanidermatum; integrated control; neem products; tomato; damping-off. DOI: 10.3329/bjar.v35i1.5862 Bangladesh J. Agril. Res. 35(1) : 11-16, March 2010